Ornamen Indramayu sebagai Ragam Hias pada Becak Jakarta - Wulandari, Sari (Bina Nusantara University, 2014)
Indramayu ornaments that are painted on Jakarta’s pedicabs have an exotic impression and a special attraction to the foreign tourists. The decorative ornament has the potential to be a valuable asset for the improvement of Indonesia art and design. The study was conducted with a qualitative research method of determining the location of culture through the stages of research, determination of informants, data collection and data analysis that were done by organizing, sorting, classifying and categorizing the data. Categorization is done based on the body parts of tricycles and obtained a variety of motives according to the space of placement the ornaments. By documenting and studying these ornaments, it can be improved due to nowaday needs, which would certainly enriches Indonesian decorative ornaments and utilized in broader needs.